Method for providing conductive surface on non-conductive polymer surface

By performing hydrophilic treatment on the polymer surface and covalent bonding of metal ions, problems such as toxicity, expensiveness, and high energy consumption when plating metal layers in the prior art are solved, and rapid, low-temperature and sustainable high-adhesion metal coating formation are achieved.

CN119836490APending Publication Date: 2025-04-15CIRRUS MATERIAL TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380063717.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-07
Filing Date
2023-09-07
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The prior art is toxic, expensive, energy-consuming, time-consuming when plating metal layers on polymer surfaces, and lacks fast, low-temperature and sustainable processes.

Method used

By performing hydrophilic treatment on a non-conductive polymer substrate, it is brought into contact with the metal ion solution, and by applying energy, the metal ions are covalently bonded to the polymer surface to form an activated surface, and then contacting the electroless plating solution to form a conductive metal surface.

Benefits of technology

The rapid, low temperature and sustainable formation of high adhesion metal coatings on the polymer surface is achieved, reducing the toxicity and energy consumption of the process, and is suitable for a wide range of polymer substrates.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119836490A_ABST
    Figure CN119836490A_ABST
Patent Text Reader

Abstract

The present invention relates to a method for providing an electrically conductive surface on a non-electrically conductive surface, in particular a polymeric surface. In particular, the method involves attaching silver ions to the polymeric surface to promote adhesion of the metal layer to the polymeric surface.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for providing a conductive surface on a non-conductive surface, especially a polymer surface. In particular, the method involves attaching silver ions to the polymer surface to promote adhesion of a metal layer to the polymer surface. Background Art

[0002] Modern engineering polymers are used in a variety of industries around the world. Electroplating is a common method for surface treatment of polymer parts to achieve chemical and wear protection, improved surface hardness, conductivity, EMI shielding or decorative appearance. However, polymer substrates are non-conductive and cannot be directly electroplated, so pretreatment is required before electroplating.

[0003] Conventional methods for metallizing non-conductive polymer substrates include four major steps, including etching, catalysis, electroless plating, and treatment with the selected electroplated metal.

[0004] Etching generally produces a rough hydrophilic surface containing micron / nanopores. This step not only prepares the polymer substrate for subsequent wet processes, but is also necessary for producing holes that use mechanical interlocking to enhance coating adhesion. Widely used etchants contain chromium trioxide (hexavalent chromium material) and sulfuric acid. However, hexavalent chromium has many health and environmental issues and requires complex processing before removal. Therefore, chromium-free etchants are preferred, and there are many patents protecting the formulations and processes of chromium-free etchants. Permanganate is a strong oxidant and non-toxic, so it is an ideal substitute for chromic acid etchants. However, the acidic environment required to ensure the oxidation capacity of the solution and the etching performance can easily decompose permanganate. The instability of this permanganate reduces its performance and hinders widespread use. U.S. Patent No. 9,657,226 discloses an acidic permanganate etchant and a stabilization method thereof. Despite many improvements, chromic acid-free etching in the prior art is still highly dependent on producing a dense and porous polymer surface to achieve mechanical interlocking between the metal layer and the polymer substrate.

[0005] After etching, the polymer substrate is catalyzed for subsequent electroless plating. In addition, the prior art includes many catalytic processes and methods, in which palladium is generally used as a catalyst. Palladium is expensive, and the traditional process generally uses three sub-steps of sensitization, catalysis and activation. Although the catalytic process is improved to a two-step method by using colloidal palladium, cleaning is still required between steps and the unstable catalytic bath needs to be carefully maintained, making the process less sustainable. Silver (Ag) is a well-known low-cost alternative to palladium (Pd), but the prior art generally requires a Sn sensitization step before Ag activation. The prior art mentions adding a silver ion catalyst in the etching step (as proposed in EP09013498B1), but the process still requires a subsequent chemical step to activate the catalyst.

[0006] WO2018208177A1 proposes a method for directly introducing silver nanoparticles into a polymer by reducing silver ions to silver metal using polymer chemical energy without an external reducing agent. This method is mainly applicable to polymer precursors and does not provide a method for reactivating polymerized materials.

[0007] Recently, a new generation of polymer plating has been developed (disclosed in US20210238748A1). This process changes the surface chemistry of the polymer by chemically attaching other long-chain polymers to the surface. The chemical attachment and vertically arranged dense long chains promote coating adhesion through mechanical interlocking without etching the polymer surface. The disclosed process still requires catalysis to support electroless metal deposition.

[0008] Currently, existing techniques for plating on polymer substrates are toxic, expensive, energy intensive, time consuming, and are generally specific to a narrow range of polymer substrates.Therefore, there is a need in the art for a fast, low temperature, sustainable polymer plating process to form an adherent metal coating.

[0009] It is clearly understood that if a prior art publication is referred to herein, this reference does not constitute an admission that the publication forms part of the common general knowledge in the art in New Zealand or any other country. Summary of the invention

[0010] In a first aspect, the present disclosure provides a conductive surface on a non-conductive substrate, comprising the steps of:

[0011] a. Providing a non-conductive substrate;

[0012] b. adjusting the non-conductive substrate with a hydrophilic agent so that the substrate is hydrophilic;

[0013] c. contacting the non-conductive substrate with an aqueous solution containing metal ions;

[0014] d. covalently bonding the metal ions to the conditioned non-conductive substrate by applying energy to form an activated substrate surface comprising metal ion seeds; and

[0015] e. contacting the activated substrate surface with an electroless plating solution comprising a plating metal salt and a reducing agent suitable for reducing both the plating metal salt and the metal ion seeds on the activated substrate surface, thereby forming a conductive surface on the non-conductive substrate.

[0016] In one example, the non-conductive substrate is a polymer substrate.

[0017] In one example, the adjusted chemical bonds on the surface of the non-conductive substrate include a percentage of carbon-carbon double bonds of about 10% to about 50% of the carbon backbone of the substrate.

[0018] In one example, the hydrophilic agent is a solution comprising a permanganate, an acid, and a complexing agent derived from a phosphorus-containing substance, the solution having about 0.01 mol / L to about 1 mol / L of phosphorus-containing anion groups.

[0019] In one example, the step of conditioning the hydrophilic agent is performed for about 5 minutes to about 20 minutes.

[0020] In one example, the aqueous solution comprising metal ions further comprises a complexing agent and optionally a surfactant.

[0021] In one example, the complexing agent can be an ammonium ion.

[0022] In one example, the surfactant, if present, can be polyvinylpyrrolidone (PVP).

[0023] In one example, the aqueous solution comprising metal ions is maintained at a temperature of about 10 degrees Celsius to about 40 degrees Celsius.

[0024] In one example, the non-conductive substrate is contacted with an aqueous solution comprising metal ions.

[0025] In one example, the contact time between the substrate and the aqueous solution is from about 1 minute to about 10 minutes.

[0026] In one example, an aqueous solution containing metal ions is sprayed onto a non-conductive substrate.

[0027] In one example, the aqueous solution containing metal ions contains one or more of AgNO 3 , CuSO 4 , NiSO 4 , or CuCl 2 at a concentration of about 0.005 mol / L to about 0.1 mol / L.

[0028] In one example, the energy source is heat and the temperature is about 60 degrees Celsius to about 90 degrees Celsius.

[0029] In one example, the energy source is applied as a stream of thermal air or a heated air environment.

[0030] In one example, the energy source is applied for a contact time of about 2 minutes to about 10 minutes.

[0031] In one example, the metal is Ag and the electroless plating solution includes electroless nickel boron and a reducing agent amine borane.

[0032] In one example, the metal is Ag and the electroless plating solution contains copper and the reducing agent is selected from formaldehyde or amine borane.

[0033] In one example, the present disclosure provides a conductive metal surface comprising a hydrophilicity-adjusted non-conductive substrate, an activated metal seed, an electroless metal-deposited metal surface, and an electroplated metal surface.

[0034] In one example, the density of activated metal seeds on the non-conductive substrate is sufficient to produce a bond strength of 10 N / cm or more when tested according to ASTM B533.

[0035] The conductive metal surface comprises a hydrophilicity-adjusted non-conductive substrate, an activated metal seed, an electroless metal-deposited metal surface, and an electroplated metal surface, the conductive metal surface being produced according to any of the aspects and examples disclosed herein.

[0036] According to aspects exemplified herein, a method for metallizing a chemically conditioned substrate is provided. In one step of the process, the substrate is hydrophilized using metal adsorption functional groups. The substrate may be selected from one or more long-chain polymers containing double-bonded carbon atoms.

[0037] In one step, the conditioning step may also include or comprise destressing the polymer substrate. The destressing process may comprise a heat treatment step. Alternatively, the destressing step may comprise immersion in an organic solvent such as, but not limited to, acetic acid or acetone.

[0038] The conditioning step may include or comprise hydrophilizing the destressed substrate using a solution whose composition is selected based on the properties of the substrate. In one example, the hydrophilizing agent may include a stable potassium permanganate salt, an acid, and a phosphorus source including a phosphate or a pyrophosphate. The conditioning step may be operated at a temperature of about 25 degrees Celsius to about 45 degrees Celsius.

[0039] In one example, the conditioning step may include a manganese dioxide removal step, for example using oxalic acid and / or sulfuric acid solutions.

[0040] In one embodiment, the polymer substrate is contacted for about 1 minute to about 10 minutes by dipping or spraying a metal-containing solution containing monovalent or divalent ions. In one example, the catalyst ions may require an activation step.

[0041] In a preferred embodiment, the metal ion source is an aqueous silver nitrate solution. The functional group introduced during the adjustment step can cause the metal ions to be adsorbed. Without wishing to be bound by any particular theory, the hydrogen atoms on the adjusted polymer surface may exchange with the metal ions during this step. In subsequent steps, the influence of external energy activates the metal ions and strengthens the bonding between the polymer surface and the metal ions. After a period of time (preferably from about 1 minute to about 10 minutes), the polymer chains redirect the hydroxyl groups and couple the metal seeds to the polymer surface.

[0042] Alternatively, the catalyst bath may contain a surfactant. The inclusion of a surfactant enables uniform seeding of the polymer surface with metal ions.

[0043] A one-step or two-step activation process can be used to promote the reorientation of the metal seeded hydroxyl groups on the polymer surface. Preferred embodiments use a slow stream of hot air. An alternative activation step comprises a two-step process that includes slow air drying followed by heat treatment in an oven.

[0044] Commercially available electroless plating baths and electroplating baths produce one or more of a conductive metal coating that is compatible with the metal seeds on the conditioned polymer surface. In one embodiment, the metallized polymer is post-treated to enhance adhesion between the metal coating and the polymer substrate through covalent bonds. The post-treatment step includes heat treatment for a period of about 1 hour to about 5 hours, or aging at ambient conditions for about 5 days to about 10 days.

[0045] It should be understood that both the foregoing general description and the following detailed description are exemplary and explanatory and do not restrict the invention as claimed. In this specification and claims, the word "comprising" and its derivatives (including "comprises" and "comprise") include each of the elements described, but do not exclude the inclusion of one or more other elements.

[0046] It is to be understood that references herein to "preferred" or "preferably" are intended to be examples only. The specification filed and the appended claims are hereby incorporated by reference into the text of the specification.

[0047] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate several embodiments of the invention and, together with the description, serve to explain the principles of the invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 : is a flow chart of a method for metallizing a non-conductive surface

[0049] Figure 2 : Shows the results of the ASTM D3359 cross-hatch test on various substrates.

[0050] Figure 3 : shows the results of a peel test according to ASTM B533 on a metal surface deposited according to aspects of the present invention

[0051] Figure 4 : Shows the ASTM D3359 cross-hatch test on ABS treated with various activation enhancement treatments

[0052] Figure 5 : XPS analysis of the activated ABS surface, showing the chemical bonding information between the polymer and the metal seed

[0053] Figure 6 : is a SEM of ABS (left) and PPS (right) polymers conditioned according to aspects of the present invention

[0054] Figure 7 :SEM image of a conventionally etched polymer substrate

[0055] Figure 8 : XPS analysis of activated PPS surface

[0056] Fig. 9 : are surface and cross-sectional images showing a PPS-CF substrate formed by the disclosed process showing metal adhesion.

[0057] Reference will now be made in detail to the preferred embodiments of the present disclosure, examples of which are illustrated in the accompanying drawings.

[0058] definition

[0059] In each instance herein, in the description and examples of the present invention, the terms "comprising", "including", etc. should be interpreted expansively, rather than restrictively. Therefore, unless the context clearly requires otherwise, throughout the specification and claims, the words "comprise", "comprising", etc. should be interpreted as being inclusive, as opposed to being exclusive, i.e., in the sense of "including but not limited to".

[0060] The term "about" or "approximately" generally means within 20%, more preferably within 10%, and most preferably within 5% of a given value or a given range. Alternatively, the term "about" means within the logarithm (i.e., order of magnitude) of a given value, preferably within twice the given value. DETAILED DESCRIPTION

[0061] Figure 1 An exemplary method of producing a metal coating on a non-conductive polymer substrate is illustrated.

[0062] At block 102 , the method begins.

[0063] At frame 104, the method adjusts the polymer substrate. The adjustment step prepares, for example, but not limited to, a polymer substrate surface for bonding to metal ions. The adjustment step produces a hydrophilic surface on the polymer substrate and produces functional groups that easily absorb metal ions. The polymer substrate can be a single polymer or copolymer, or can be reinforced with glass fiber, carbon fiber or other reinforcing materials known in the art. Preferred polymer chains contain easily oxidized functional groups, such as double bond carbons found in hydrocarbons containing vinyl groups or benzyl rings and sulfides. The preferred structure is shown below. Polyesters and polymers containing only CC single bonds are less preferred. However, blends with preferred polymers can be selected. The polymer substrate can be selected from acrylonitrile butadiene styrene (ABS), polyamide (PA), polyphenylene sulfide (PPS), phenolic resins or blends of these polymers.

[0064]

[0065] The polymer substrate can be produced by injection molding, 3D printing or other such methods that produce the desired final product shape. The polymer substrate can be solid or contain blind holes, openings or channels or other features suitable for the final application. In one example, the adjustment step can include or include stress relief of the substrate. The stress relief process is selected based on the polymer substrate shape, its composition and processing conditions. The stress relief treatment may preferably include heat treatment between 60 degrees Celsius and 75 degrees Celsius for 0 to 2 hours. The heat treatment can be carried out in an oven or in hot water. In one example, the stress relief process may include immersion in an organic solvent at 15 degrees Celsius to 30 degrees Celsius for 0.5 minutes to 30 minutes. An example of such an organic solvent may be acetic acid. In another example, the organic solvent may be 25% acetone.

[0066] In one example, the adjustment step can include making the polymer substrate hydrophilic after stress relief. Based on the polymer substrate chemical properties, the hydrophilic agent bath composition is selected because the hydrophilic agent selectively destroys the polymer chain and attaches the active functional group to the polymer chain. These active functional groups enhance the hydrophilicity of the polymer substrate. The hydrophilic group has an affinity for metal ions so that the metal ions are adsorbed and bonded to the polymer chain. The hydrophilic functional group can be selected from polar groups, such as hydroxyl, sulfonic acid and carbonyl and other groups known in the art.

[0067] In one example, the polymer substrate is ABS, the conditioning step includes a hydrophilization step, and the hydrophilization solution comprises at least one permanganate, an acid, and a source of a phosphorus-containing substance selected from phosphates and pyrophosphates. The permanganate can be selected from those permanganates dissolved in aqueous solution well known in the art, preferably potassium permanganate or sodium permanganate. The concentration of the permanganate is 10 g / L to 200 g / L or the maximum solubility of the specific permanganate. The acid can be an inorganic acid or an organic acid. The inorganic acid can be sulfuric acid, nitric acid or phosphoric acid. The organic acid can be acetic acid. The concentration of the acid is 3.8 mol / L to 10 mol / L for a monoprotic acid. The phosphorus-containing substance can be a phosphate, a hydrogen phosphate, a dihydrogen phosphate or a pyrophosphate. The concentration of the phosphorus-containing substance is 0.05 mol / L to 1 mol / L. The hydrophilizing agent can be operated at 25 degrees Celsius to 45 degrees Celsius for 5 minutes to 20 minutes.

[0068] Permanganate is a strong oxidant, and its oxidizing power is further enhanced in an acidic environment or increases with the decrease of solution pH. Compared with conventional chrome etchants, permanganate is environmentally friendly and does not have health problems while maintaining sufficient oxidizing power. However, permanganate is easily decomposed, especially in acidic solutions, to form divalent manganese ions and manganese dioxide. Divalent manganese ions further catalyze and thus accelerate the decomposition of permanganate. Complexing divalent manganese ions with stabilizers reduces their effect on permanganate anions, thereby inhibiting the decomposition of permanganate. In an oxidizing environment, inorganic substances are superior to organic substances because organic substances can be destroyed by permanganate. In this case, phosphates and pyrophosphates are preferred complexing agents. In the presence of a complexing agent, the service life of the permanganate hydrophilic agent can be extended.

[0069] In an example, the adjusting step comprises a method for removing the residual manganese dioxide produced in the previous step. In an example, the substrate is immersed in a solution of oxalic acid comprising 5g / L to 20g / L and 5 volume % to 15 volume % of sulfuric acid. The manganese dioxide removal step can be carried out by soaking or by supersonic treatment. In an example, the manganese dioxide removal solution is operated at 30 degrees Celsius to 80 degrees Celsius, preferably 50 degrees Celsius to 60 degrees Celsius for 0.5 minute to 10 minutes, preferably 2 minutes to 5 minutes. In an example, the removal step is operated at 1 minute to 5 minutes, preferably 3 minutes in supersonic treatment.

[0070] At block 106, the method includes contacting the conditioned polymer surface with a solution containing metal ions. In one example, the substrate is immersed in a bath to contact the solution, in an alternative example, the solution is sprayed on the substrate. In principle, the metal ion can be any monovalent or divalent metal ion suitable for catalyzing the electroless reduction of the coating metal, such metal ions include Ag+, Ni + 、Ni2+ , Cu + , Cu 2+ 、Co + 、Co 2+ etc. Monovalent ions are preferred over divalent ions because the hydrophilic hydroxyl groups introduced on the polymer surface can reduce the monovalent ions. Divalent ions may require the addition of a reducing chemical to complete the further step of reduction. The reducing chemical will depend on the ion selected. The preferred monovalent ion is silver.

[0071] The solution comprising the metal ion source is an aqueous solution, and the Ag ion source can be selected from water-soluble Ag salts. In a preferred example, the Ag ion source is silver nitrate and the concentration in the bath is 0.005mol / L to 0.1mol / L, preferably 0.01mol / L to 0.05mol / L. The preferred concentration of the silver ion source is determined by the plating rate of the subsequent electroless deposition step. In an alternative example, the silver ion is complexed, and the complexing agent is an ammonium ion, and the complexing silver ion source helps to extend the life of the solution containing the metal ion. In an alternative example, the silver ion is stabilized with polyvinyl pyrrolidone (PVP) to minimize the agglomeration of the silver nanoparticles when activated.

[0072] Although not wishing to be bound by theory, the inventors understand that polar functional groups (e.g., hydroxyl or carboxyl) are introduced into the polymer chain during the conditioning step. When contacted with a solution containing a monovalent metal ion, the metal ion is absorbed on the hydrophilic polymer surface. In subsequent steps, under the influence of an external energy source, the hydride ions from the functional groups exchange positions with the reduced monovalent metal ions. At other locations on the polymer surface, the monovalent metal ions are reduced but not attached to the surface, which will not contribute to coating adhesion. At the same time, water molecules attached to the polymer chain or trapped in the polymer matrix are driven away, thereby improving the bonding strength between the metal atom and the polymer. Over time, the polymer chain redirects the hydroxyl groups pointing outward to minimize the surface energy, which tightly couples the attached metal particles to the polymer surface.

[0073] In a preferred embodiment, the metal ion bath is at room temperature, alternatively, the catalyst ion bath can be at any temperature of 10 degrees Celsius to 40 degrees Celsius. The temperature is selected to maximize the life of the metal ion solution and optimize the reaction between the metal ions and the hydrophilic groups on the substrate. The sufficient time for the metal ions to be adsorbed onto the hydrophilic groups is 1 minute to 10 minutes, preferably 5 minutes. Excessive contact time between the substrate and the metal ion solution adsorbs too many metal ions on the surface, which may cause excessive reaction rate in the subsequent electroless deposition step.

[0074] In one example, the substrate is ABS, the metal ion bath contains 2 g / L silver nitrate, and the contacting process is operated at room temperature for 10 minutes.

[0075] In an alternative example, the metal ion bath contains 8 g / L silver nitrate and a liquid polymer / surfactant, such as 40 g / L polyvinyl pyrrolidone, to enable more uniform seeding of the metal ions on the polymer surface.

[0076] In an alternative example, the metal ion bath contains 0.3 mol / L cuprous chloride and 5.2 mol / L hydrochloric acid to increase the solubility of cuprous chloride.

[0077] In an alternative example, the catalyst metal bath contains 0.1 mol / L to 0.2 mol / L of copper ions. The copper ions may be derived from copper sulfate, copper acetate, or any water-soluble copper salt known in the art.

[0078] At frame 108, the method enhances the metal ions on the substrate. The enhancement step reduces the metal ions and fixes them to the polymer substrate. Although the reduction of the metal ions can occur naturally over time, the process can be accelerated by external energy (e.g., heat). The enhancement process may include one or two steps. In a preferred embodiment, the enhancement step adopts a low-speed hot air stream at a temperature of 60 degrees Celsius to 90 degrees Celsius for 2 minutes to 10 minutes, preferably a flow rate of 15m / s and a temperature of 80 degrees Celsius and 3 minutes. In an alternative example, the two-step activation includes drying in a low-speed compressed air stream at room temperature, then heat-treating in an oven at 60 degrees Celsius to 90 degrees Celsius for 5 minutes to 10 minutes. In an example, the activated substrate is stored for 1 hour before the next step, so that the Ag nanoparticles of reduction are further integrated into the polymer substrate.

[0079] At block 110, the method deposits a conductive surface on a polymer substrate from an electroless plating bath compatible with the metal catalytic seed. The electroless plating bath may be selected from a commercial nickel plating bath or a commercial copper plating bath to produce a nickel conductive layer or a copper conductive layer. In one example, the electroless plating bath contains 50 g / L nickel sulfate hexahydrate, 100 g / L sodium pyrophosphate, and 3 g / L dimethylamine borane, and is operated at 25 degrees Celsius to 40 degrees Celsius, and the polymer substrate is completely covered with a conductive layer within 30 minutes.

[0080] At block 112, the method electroplates the substrate with one or more layers of a surface metal selected according to the desired component function. The metal layer may include a single metal layer or metal alloy layer, or multiple metal layers or metal alloy layers. The metal coating may be selected from nickel, copper, tin, cobalt, and nickel-zinc alloys, etc., with various matte to full bright finishes.

[0081] At block 114, the method post-treats the metallized polymer surface to increase adhesion between the metal coating and the substrate. The post-treatment may include heat treatment at about 40 degrees Celsius to about 70 degrees Celsius for about 1 hour to about 3 hours, or aging at ambient conditions for about 1 week, or a combination of these two steps. The post-treatment further improves coating adhesion by eliminating moisture trapped in the polymer substrate.

[0082] Adhesion between polymer substrate and metal surface is formed by covalent bonds between metal atoms and polymer surface. These covalent bonds are initially produced by hydroxyl groups or carboxyl groups introduced on polymer surface by conditioning step. Conditioning step introduces new functional groups by breaking bonds on one or more surface polymers and attaching functional groups to backbone sites. Metal ions are reduced by new functional groups shown in the following formula.

[0083] In subsequent steps, the initial bond of the catalyst atoms to the substrate can be improved by the rearrangement of the polymer chain to better integrate the metal nanoparticles. The process is shown in the following formula. The process occurs naturally over time, or can be accelerated by applying heat. In one example, the metal-coated substrate is heat-treated at a temperature of about 40°C to about 100°C, preferably about 60°C for a period of about 10 minutes to about 2 hours, preferably about 30 minutes. In an alternative example, the metallized polymer substrate is naturally aged at room temperature for a period of about 12 hours to about 72 hours, preferably about 24 hours.

[0084] Example:

[0085] The following examples indicate specific operating conditions and illustrate the practice of the present disclosure. However, these examples should not be considered to limit the scope of the present disclosure. The examples are selected to specifically illustrate aspects of polymer surface activation, attachment, to achieve adherent metal coatings on metal seeds.

[0086] Example 1 Adjustment process

[0087] The tuning depends on the polymer substrate, and the examples provided herein discuss tuning according to aspects of the present invention for a variety of commercially important substrates.

[0088] Conditioning breaks the polymer chains on the substrate surface and introduces hydrophilic functional groups onto the substrate surface. Although conditioning can also etch the surface, it is not necessary to form a very rough surface for coating adhesion. The conditioning step includes an optional stress relief step and a hydrophilization step. If the hydrophilizing agent solution is permanganate based, a MnO2 removal step may be required. The effectiveness of the conditioning process can be measured by wettability testing. A polymer surface is considered to be fully conditioned if its contact angle with water is less than 10°. Table 1 summarizes the conditioning parameters for various polymer substrates.

[0089] Table 1. Tuning parameters for various polymer substrates

[0090]

[0091] Example 2: Metal implantation and first metallization

[0092] The choice of metal ion and the activation process depends on the functional groups generated on the polymer by the conditioning step and the electroless plating bath selected for the subsequent first metallization step.The examples provided herein discuss metal implantation according to aspects of the present invention.

[0093] In one example, the conditioned ABS sample is activated with Ag and plated with an electroless Ni bath. The ABS sample is first conditioned in a solution containing 20 g / L KMnO4 and 20% by volume H2SO4. The conditioning step is performed at about 35°C for about 10 minutes. The residual MnO2 produced from the conditioning step is then removed in a solution containing 10 g / L oxalic acid and 10% sulfuric acid, operating at about 50°C for about 2 minutes. The ABS sample is then rinsed with deionized water and immersed in a solution containing 10 g / L silver nitrate for 10 minutes at room temperature. After immersion, the ABS sample is treated in a hot air stream at about 70°C until the surface is dry, usually taking about 2 minutes. Finally, the ABS sample is immersed in an electroless Ni-B bath containing 50 g / L nickel sulfate hexahydrate, 100 g / L sodium pyrophosphate, and 3 g / L dimethylamine borane. The electroless Ni-B is operated at about 30°C for about 30 minutes. The ABS coupons were fully plated with a conductive Ni layer and were ready for subsequent electroplating with the metal of choice.

[0094] In another example, the conditioned ABS is activated with Cu and plated with an electroless Cu bath. The ABS sample is conditioned from the method detailed above. The ABS sample is then immersed in a solution comprising cuprous chloride and chloric acid for about 10 minutes. The ABS sample is then enhanced in a stream of hot air and plated with electroless Ni, as detailed above.

[0095] In another example, a PPS sample was activated with Cu and plated with an electroless Ni bath. The PPS sample was first conditioned in a solution containing 20 g / L KMnO4 and 40% H2SO4. The conditioning was operated at about 27°C for about 30 min. The residual MnO2 produced from the conditioning step was then removed in a solution containing 10 g / L oxalic acid and 10% sulfuric acid, operated at about 50°C and ultrasonically treated for about 2 minutes. After rinsing with deionized water, the PPS sample was immersed in a solution containing cuprous ions. A cuprous solution was prepared by mixing an ascorbic acid solution with a copper sulfate solution, which contained 0.125 mol / L Cu and 0.002 mol / L ascorbic acid. The PPS sample was then rinsed with deionized water and plated with electroless Cu containing 50 mmol / L EDTA, 50 mmol / L cupric chloride, 0.1 mol / L boric acid, and 0.1 mol / L DMAB. Table 2 summarizes the activation parameters using various metal ion sources.

[0096] Table 2. Activation parameters of various metal ions

[0097]

[0098] Example 3: Coating Process Performance

[0099] The purpose of the disclosed method is to produce an adherent metal coating on a polymer surface. Two common measurement methods for coating adhesion are the quantitative peel test and the qualitative cross-hatch test. The peel test is performed according to ASTM B533, where the results are continuously recorded in Newtons / cm during the peel period and are expressed as the peak value, average value and standard deviation of the test. The cross-hatch test is performed according to ASTM D3359, and the qualitative results are recorded as 0B to 5B, where 5B is the best adhesion with 0% coating removal.

[0100] In the following examples, methods of forming adherent metal coatings on a number of commercially important polymer surfaces are described in accordance with certain aspects of the present invention.

[0101] In one example, an ABS sample was plated with electroless Ni according to the method detailed in Example 2, and then electroplated with bright Ni. The bright Ni bath contained 270 g / L nickel sulfate, 60 g / L nickel chloride, 40 g / L boric acid, and commercially available additives. The bright nickel was plated at about 4 A / dm 2 Plating was performed for about 20 minutes to produce a nickel coating of about 16 μm thick. Cross-hatch testing according to ASTM D3359 showed excellent coating adhesion, classified as 5B (Figure 201).

[0102] In one example, an ABS sample was plated with electroless Ni according to the method detailed in Example 2 and then electroplated with bright Cu. The bright Cu bath contained 195 g / L copper sulfate, 75 g / L sulfuric acid, and commercially available additives. The bright Cu plating was carried out at about 4 A / dm 2 The operation was about 100 minutes to produce a copper coating of about 44 μm. The copper-plated ABS specimen was conditioned at about 70° C. for about 1 hour before peel strength testing according to ASTM B533 ( FIG. 301 ). The average peel strength of 19.2 N / cm showed excellent coating adhesion ( FIG. 302 ).

[0103] In another example, a PPS sample reinforced with glass fiber (PPS-GF) is first conditioned in a solution comprising 20 g / L KMnO4 and 40% by volume H2SO4. The conditioning is operated at about 27°C for about 30 minutes. The residual MnO2 produced from the conditioning step is then removed in a solution comprising 10 g / L oxalic acid and 10% sulfuric acid, operated at about 50°C and ultrasonically treated for about 2 minutes. After rinsing with deionized water, the PPS-GF sample is then rinsed with deionized water and immersed in a solution comprising 2 g / L of silver nitrate for about 10 minutes at room temperature. After immersion, the PPS-GF sample is treated in a hot air stream at about 70°C until the surface is dry. Finally, the PPS-GF sample is plated with about 10 μm of electroless Ni and electrolytic Ni. The Ni coating is classified as 5B (Figure 202) by the cross-hatch test according to ASTM D3359.

[0104] In another example, the PETG sample is first conditioned in a solution comprising 20 g / L KMnO4 and 40% by volume H2SO4. The conditioning is operated at about 27°C for about 1 hour. The residual MnO2 produced from the conditioning step is then removed in a solution comprising 10 g / L oxalic acid and 10% sulfuric acid, operating at about 50°C for about 2 minutes. The PETG sample is then rinsed with deionized water and immersed in a solution comprising 2 g / L silver nitrate for about 10 minutes at room temperature. After immersion, the PETG sample is treated in a hot air stream at about 70°C until the surface is dry. Finally, the PPS sample is plated with or without electroplated Ni. The Ni coating is classified as 5B (Figure 203) by the cross-hatch test according to ASTM D3359.

[0105] In another example, the PA6 specimen was first conditioned in a solution containing 20% ​​sulfuric acid at about 20 degrees Celsius for about 20 seconds. After rinsing with deionized water, the conditioned PA6 specimen was then immersed in a solution containing 2 g / L of silver nitrate at room temperature for about 10 minutes. The PA6 specimen was then activated in a hot air stream at about 70 degrees Celsius until the surface was dry. Finally, the PA6 specimen was plated with about 10 μm of electroless Ni and electrolytic Ni. According to ASTM D3359, the Ni coating adhesion was classified as 5B.

[0106] In another example, a paper reinforced phenolic resin sample was first conditioned in a solution containing 20 g / L potassium permanganate and 20% sulfuric acid at about 35 degrees Celsius for about 15 minutes. Residual MnO2 was removed in a solution containing 10 g / L oxalic acid and 10% sulfuric acid at about 50 degrees Celsius for about 2 minutes. After rinsing in deionized water, the conditioned paper reinforced phenolic resin sample was immersed in a solution containing 2 g / L silver nitrate at room temperature for about 5 minutes. The paper reinforced phenolic resin was then treated in a hot air stream at about 70 degrees Celsius for about 2 minutes. The activated paper reinforced phenolic resin was finally plated with about 10 μm of electroless Ni and electrolytic Ni. According to ASTM D3359, the Ni coating adhesion was classified as 5B. Table 3 summarizes the coating adhesion results for various polymer substrates.

[0107] Table 3. Coating Adhesion of Various Metallized Polymer Substrates

[0108]

[0109] Example 4: Activation Performance

[0110] Methods for activating polymer surfaces for electroless plating by an external heat source are described herein. The following examples show how heat treatment can result in coating adhesion.

[0111] The ABS specimens in this example were conditioned as detailed in Table 3 and immersed in a solution containing 10 g / L silver nitrate for approximately 10 minutes at room temperature.

[0112] In one example, the ABS coupons were then left at ambient conditions until dry and then plated with electroless Ni and electrolytic Ni. Cross-hatch testing according to ASTM showed coating adhesion, classified as 1 B (Figure 401).

[0113] In one example, an ABS coupon was activated in a stream of hot air at about 70C and left for about 1 hour prior to electroless Ni and electrolytic Ni plating. The coating had excellent adhesion, classified as 5B (Fig. 402).

[0114] In one example, cold air was used to blow excess Ag solution off the ABS coupon, and the coupon was heat treated in an oven at about 60° C. for about 5 min prior to electroless Ni and electrolytic Ni plating. The coating had excellent adhesion, classified as 5B ( FIG. 403 ).

[0115] In one example, cold air was used to blow excess Ag solution off the ABS coupons, and the coupons were heat treated in an oven at about 40° C. for about 5 min prior to electroless Ni and electrolytic Ni plating. The coatings exhibited good adhesion, classified as 4B (Figure 404).

[0116] The above examples show that various forms of heat treatment significantly improve the adhesion of the metal coating to the ABS substrate. XPS analysis only detected COO-Ag bonds ( Figure 5 504, Figure 5 505 and Figure 5 506). The ABS surface conditioned according to aspects of the present disclosure exhibits only widely dispersed relatively deep pores (Fig. 603), depicted in the SEM image (Fig. 601). In contrast, the polymer surface etched according to the prior art exhibits a dense, deep porous structure (Fig. Figure 7 701), which is required for the formation of mechanical interlocking (JS Seo et al., Surfaces and Interfaces, Vol. 26, 2021). Therefore, it can be inferred that the chemical bonds generated in the heat treatment step r dominate the coating adhesion mechanism.

[0117] Example 5: Metal Bonding to Sulfonic Acid Functional Groups on PPS Substrate

[0118] PPS has traditionally been a very difficult substrate to form adherent metal coatings on and mechanical etching often provided the only viable approach. The examples show that hydrophilization in a permanganate, sulfuric acid based solution effectively forms sulfonic acid functional groups to which silver covalently bonds after thermal activation.

[0119] Figure 8 801 shows aromatic polymer features (803) corresponding to benzyl rings of the hydrophilized substrate. Figure 8 802 shows that the metal seed is bound to the PPS polymer surface via a covalent bond between Ag and the (-C6H4S-) functional group (804).

[0120] Figure 8 The 805 provides concentration data of metal seeds on the polymer surface and at a depth of 15 nm from the surface. The increased concentration of metal seeds at the subsurface confirms the enhancement process described in this invention, namely the reorientation of polar groups and the associated movement of metal seeds into the polymer subsurface.

[0121] The foregoing description is exemplary only and may be varied significantly without departing from the scope of the present disclosure. For example, a variety of hydrophilic baths and methods will produce the same polar groups on the polymer surface, a variety of monovalent and divalent metal ionic species will effectively bond to the active polar groups; and a variety of external energy sources will be used to activate the bonds between the polar groups and the metal ionic species.

[0122] Example 6: Adhesion test on PPS-CF substrate

[0123] As described in Example 5, a PPS-CF (carbon fiber) substrate is an inherently difficult surface to form an adherent metal coating on. Previous examples have shown that hydrophilization in a permanganate, sulfuric acid-based solution effectively forms sulfonic acid functional groups to which silver covalently bonds after thermal activation. Here, we demonstrate adherent plating on this activated surface.

[0124] The activated PPS-CF specimen was then immersed in an electroless Ni plating bath. Fig. 9 ) is about 9 μm thick (901) and exhibits excellent adhesion (902). Image (901) shows that the Ni coating adheres not only to the PPS matrix, but also to the carbon fiber filler in the composite.

[0125] Cross-hatch testing was performed according to ASTM D3359, with qualitative results reported as 0B to 5B, with 5B being the best adhesion with 0% coating removal.

[0126] Features described with respect to one example may be applied to other examples, or combined or interchanged with features of other examples, as appropriate, without departing from the scope of the present disclosure.

[0127] The present disclosure in its preferred form provides the advantages of greater adhesion, higher energy efficiency, and shorter processing times; and provides an inherently safer process due to lower processing temperatures and elimination of toxic chemicals than processes commonly used in the prior art.

[0128] Other examples of the disclosure will be apparent to those skilled in the art from consideration of the specification and practice of the forms of examples disclosed herein.The specification and examples are to be considered exemplary only, with the true scope and spirit of the disclosure being indicated by the following claims.

Claims

1. A method for providing a conductive surface on a non-conductive substrate, comprising the steps of: a. Providing a non-conductive substrate; b. adjusting the non-conductive substrate with a hydrophilic agent so that the substrate is hydrophilic; c. contacting the non-conductive substrate with an aqueous solution containing metal ions; d. covalently bonding the metal ions to the conditioned non-conductive substrate by applying energy to form an activated substrate surface comprising metal seeds; as well as e. contacting the activated substrate surface with an electroless plating solution comprising a plating metal salt and a reducing agent suitable for reducing both the plating metal salt and the metal ion seeds on the activated substrate surface, thereby forming a conductive surface on the non-conductive substrate. The method of claim 1 , wherein the non-conductive substrate is a polymer substrate.

3. The method of claim 1 or 2, wherein the adjusted chemical bonds on the surface of the non-conductive substrate include a percentage / ratio of carbon-carbon double bonds of about 10% to about 50% of the carbon backbone of the substrate.

4. The method according to any one of claims 1 to 3, wherein the hydrophilic agent is a solution comprising a permanganate, an acid and a complexing agent derived from a phosphorus-containing substance, the solution having about 0.01 mol / L to about 1 mol / L of phosphorus-containing anionic groups.

5. The method of claim 1 or 4, wherein the conditioning step with the hydrophilizing agent is performed for about 5 minutes to about 20 minutes.

6. The method of claim 1 or 5, wherein the conditioning step with the hydrophilizing agent is performed at about 25 degrees Celsius to about 45 degrees Celsius.

7. The method according to any one of claims 1 to 6, wherein the aqueous solution comprising metal ions further comprises a complexing agent and optionally a surfactant.

8. The method according to claim 7, wherein the complexing agent can be ammonium ions.

9. The method of claim 7, wherein when the surfactant is present, the surfactant may be polyvinylpyrrolidone (PVP).

10. The method of claim 7, wherein the aqueous solution comprising metal ions is maintained at a temperature of about 10 degrees Celsius to about 40 degrees Celsius.

11. The method according to any one of claims 1 to 10, wherein the non-conductive substrate is contacted with the aqueous solution comprising metal ions.

12. The method of claim 11, wherein the contact time between the substrate and the aqueous solution is from about 1 minute to about 10 minutes.

13. The method according to claim 1, wherein the aqueous solution containing metal ions is sprayed on the non-conductive substrate.

14. The method according to any one of claims 1 to 13, wherein the aqueous solution comprising metal ions comprises one or more of AgNO3, CuSO4, NiSO4 or CuCl2 at a concentration of about 0.005 mol / L to about 0.1 mol / L.

15. The method of any one of claims 1 to 14, wherein the energy source is heat and the temperature is about 60 degrees Celsius to about 90 degrees Celsius.

16. The method of claim 15, wherein the energy source is applied as a stream of hot air or a hot air environment.

17. The method of claim 15 or 16, wherein the energy source is applied for a contact time of about 2 minutes to about 10 minutes.

18. The method of any one of claims 1 to 17, wherein the metal is Ag and the electroless plating solution comprises electroless nickel boron and the reducing agent amine borane.

19. A method according to any one of claims 1 to 17, wherein the metal is Ag and the electroless plating solution comprises copper, and the reducing agent is selected from formaldehyde or amine borane.

20. Conductive metal surfaces, including hydrophilicity-adjusted non-conductive substrates, activated metal seeds, metal surfaces deposited with electroless metal, and electroplated metal surfaces.

21. The conductive metal surface on a non-conductive substrate of claim 20, wherein the density of the activated metal seeds is sufficient to produce a bond strength of 10 N / cm or higher when tested according to ASTM B533.

22. A conductive metal surface produced according to any one of claims 1 to 19, comprising a hydrophilicity adjusted non-conductive substrate, activated metal seeds, an electroless metal deposited metal surface and an electroplated metal surface.

Citation Information

Patent Citations

  • Method of metal plating of polymer-containing substrates

    US20210238748A1

  • Composition for etching treatment of resin material

    US9657226B2

  • Composite resins containing silver nanoparticles

    WO2018208177A1